1987
DOI: 10.4315/0362-028x-50.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella, Campylobacter jejuni, and Yersinia enterocolitica in Raw Milk

Abstract: Raw milk samples collected from bulk tank trucks of milk suppliers in Wisconsin, Michigan, and Illinois were analyzed for Salmonella, Campylobacter jejuni, and Yersinia enterocolitica. Salmonella spp. were isolated from 32 (4.7%) of 678 samples, and C. jejuni was found in one (0.4%) of 237 samples. Although Y. enterocolitica was recovered from 114 (48.1%) of 237 samples, all isolates were environmental, non-virulent strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Lower levels of milk contamination were recorded by Doyle and Roman (1981), who confirmed the presence of Campylobacter bacteria in 1 out of 108 raw milk samples and Gomółka and Uradziński (1996), who found C. jejuni in 2 out of 130 raw milk samples (1.5%). Similar results were obtained by Manus and Lanier (1987), who analyzed 237 raw milk samples and recovered Campylobacter in only 1 (0.4%). A higher recovery rate at the level of 12% and 12.3% were obtained by Humphrey and Hart (1988), Rohrbach et al (1992) as well as Jacobs - Reitsma (2000).…”
Section: Discussionsupporting
confidence: 72%
“…Lower levels of milk contamination were recorded by Doyle and Roman (1981), who confirmed the presence of Campylobacter bacteria in 1 out of 108 raw milk samples and Gomółka and Uradziński (1996), who found C. jejuni in 2 out of 130 raw milk samples (1.5%). Similar results were obtained by Manus and Lanier (1987), who analyzed 237 raw milk samples and recovered Campylobacter in only 1 (0.4%). A higher recovery rate at the level of 12% and 12.3% were obtained by Humphrey and Hart (1988), Rohrbach et al (1992) as well as Jacobs - Reitsma (2000).…”
Section: Discussionsupporting
confidence: 72%
“…Several surveys have detected foodborne pathogens in bulk tank milk (Davidson, 1989;Doyle and Roman, 1982;Farber et al, 1988;Fedio and Jackson, 1990;Hassan et al, 2000;Jayarao and Henning , 2001;Liewen and Plautz, 1988;Lovett et al, 1983Lovett et al, , 1987McEwen et al, 1988;McManus and Lanier, 1987;Muraoka et al, 2003;Murinda et al, 2002aMurinda et al, ,b, 2004aRohrbach et al, 1992;Slade et al, 1988;Steele et al, 1997;Van Kessel et al, 2004;Waak et al, 2002). Results of those studies have shown clearly that the prevalence of foodborne pathogens, including C. jejuni, STEC, L. monocytogenes, and Salmonella spp.…”
Section: Prevalence Of Foodborne Pathogens In Milkmentioning
confidence: 92%
“…and Yersinia enterocolitica in farm bulk tank milk (BTM) (Lovett, Francis, & Hunt, 1987;McManus & Lanier, 1987;Moustafa, Ahmed, & Marth, 1983;O'Donnell, 1995;Rahn et al, 1997;Rohrbach, Draughon, Davidson, & Oliver, 1992;Steele et al, 1997).…”
Section: Introductionmentioning
confidence: 99%